Integrating Sustainable Development Goals into Coffee Shop Operations: Insights from Kedai Kosim, Indonesia - Waskita, Gautama Sastra; Ashari, Denny Rakhmad Widi; Al Haris, Mohammad Basid; Rifa’i, Akhmad; Eldon, Mokhamad (Universitas Nahdlatul Ulama Blitar, 2024)
Integrating Sustainable Development Goals into Coffee Shop Operations: Insights from Kedai Kosim, Indonesia The integration of Sustainable Development Goals (SDGs) into small business operations remains a significant challenge, particularly for coffee shop entrepreneurs in developing countries like Indonesia. This study aims to explore how SDGs, specifically SDG 12 (Responsible Consumption and Production), SDG 13 (Climate Action), and SDG 8 (Decent Work and Economic Growth), are integrated into the operations of Kedai Kosim, a coffee shop in Tulungagung, Indonesia. Using a qualitative autoethnographic approach, the researcher immersed themselves in the business’s operations to analyze sustainability practices. The findings reveal that Kedai Kosim successfully incorporates sustainability into its daily operations by reducing waste, implementing energy-efficient technologies, and fostering local economic growth through fair trade practices. Despite initial challenges, such as high upfront costs for sustainable technologies, the business benefits from enhanced customer loyalty and long-term cost savings. The study highlights the potential for small businesses to contribute to sustainable development, offering practical insights for other coffee entrepreneurs and policymakers. Future research should explore the quantitative impacts of SDG integration and investigate the role of technology in supporting sustainable practices.